(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
In an earlier work Making Islam Democratic (2007), I attempted to interrogate the infamous question of whether Islam was compatible with democracy. I concluded that whereas Islamism (understood as deploying Islam as a political project to establish Islamic state) was unlikely to embrace democratic polity, ‘post-Islamism’ could. My early formulation of ‘post-Islamism’ was based primarily on the experience of Iran in the late 1990s. In this essay I try to see how much this concept has a broader resonance, given that Islamist movements in the Muslim world have experienced significant changes in the past three decades. Basing itself on numerous empirical studies of shift in the political Islam, the essay focuses on revisiting the concept of ‘post-Islamism’ by addressing the questions that its application to other experiences of Islamist politics may raise, as well as the questions that critiques have raised since the concept’s inception. Post-Islamism emerges as a critique from within and without of Islamist politics.